Ameliorating deleterious effects of ammonia toxicity on Oreochromis niloticus using Yucca schidigera extract as a water supplement - Mustafa A.E. Mohamed; Adel I. Attia; Usama M. Abdel Monem; Fayiz M. Reda; Hemat K. Mahmoud; Ayman S. Salah; Mahmoud M. Azzam; Alessandro Di Cerbo; Mahmoud Alagawany; Ragaa A. Ahmed; Antonia Lestingi (Aquaculture Reports)
The current study attempted to establish Yucca schidigera extract (YSE) modifying effects on long-term ammonia (NH3) poisoning in Nile Tilapia. Randomly, 300 Nile tilapia fish were divided into 5 equal groups, each including four replications. One group was retained as the standard control (1st) group, and the 2nd group was subjected to NH3 for three weeks (during the last week of the 1st, 2nd and 3rd month of the experiment), and the 3rd, 4th and 5th groups were supplemented with YSE (6, 8 and 10 mg/L water every 2 days) and subjected to NH3 for three weeks (during the last week of the 1st, 2nd and the 3rd month of the experiment), respectively. A significant improvement in water quality was recorded with YSE by increasing dissolved oxygen in the water and decreasing water pH, total ammonia nitrogen concentration, and un-ionized ammonia. Feed intake and feed conversion were improved with all groups supplemented with YSE. YSE supplementation to ammonia-polluted water of Nile tilapia significantly improved liver and kidney functions such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatinine, urea, and uric acid. YSE improved immunity and antioxidant parameters when compared to the ammonia group. Digestive enzymes were enhanced by the addition of YSE to the ammonia-polluted water of Nile tilapia. In conclusion, our investigation aimed to declare YSE modulatory effects on the quality of water, growth performance, immunological status, and antioxidant capacity in fish.